Low-Cost Carriers Socio-Economic Impact in Tourism Development: The Case of Faro’s Airport Hinterland - Rosado, Tiago (2017)
Due to airline market deregulation in Europe LCC’s (Low-Cost Carriers) depicts a fast growth in the last decade and it’s expected that this growth continues in the next years. Also, thisEuropean airline market change has affected the way many airports operate and it’s likely that thischange impacts not only airports performance and efficiency, but also its hinterland. Tourism development is one of the main beneficiaries of this new paradigm. Airport hinterland definition is very broad.Traditionally hinterland is measured by several kilometres’ radiuscentred on the airport or a certain travel time from one pointto the airport. However, this definition may be considered too simplistic because there are other indicators that can determine such influence area.Therefore, current literature prefers to do it in combination with certain pre-defined criteria: airport impact or effectiveness assessment, or a tourism destination perspective. This paper presents a study on airport hinterland socio-economic activity, with emphasis on tourism development due to LCC operations. Thestudy analyses socio-economic indicators from 2006 to 2012, a period whichrepresents the full operation entry and evolution of LCC’s in the Portuguese south airport of Faro. Results are aligned with the expectations created by literature review as well by the empirical preliminary analysis from the case study, showing a possible correlation between LCC movements and some hinterland indicators with direct impact on the tourism sector.